Palladium Nanoparticles Decorated Graphene Oxide: Active and Reusable Nanocatalyst for the Catalytic Reduction of Hexavalent Chromium(VI). Issue 27 (21st September 2017) - Celebi, Metin; Karakas, Kadir; Ertas, Ilknur Efecan; Kaya, Murat; Zahmakiran, Mehmet
Abstract: Today, the catalytic reduction of Cr(VI) to Cr(III) stands one of the most important challenges in the environmental chemistry and catalysis due to highly stable, contaminant and toxic nature of Cr(VI). In this study, we show that a new nanocatalyst system comprised of 3‐aminopropyltriethoxysilane (APTS) stabilized palladium(0) nanoparticles grafted onto the surface of graphene oxide (Pd/GO) efficiently works in the catalytic reduction of Cr(VI) to Cr(III) under mild reaction conditions. Pd/GO nanocatalyst was reproducibly prepared through two‐steps procedure: ( i ) H2 reduction of Pd(dba)2 (dba=dibenzylideneacetone) in the presence of APTS in THF to synthesize colloidal APTS stabilized palladium(0) nanoparticles and then ( ii ) the deposition of 3‐aminopropyltriethoxysilane stabilized palladium(0) nanoparticles onto the surface of graphene oxide (GO) by impregnation. The characterization of Pd/GO was carried out by advanced analytical techniques. The summation of the results acquired from these analyses reveals that the formation of well‐dispersed and highly crystalline palladium(0) nanoparticles on the surface of GO. The catalytic performance of the resulting Pd/GO in terms of activity and stability was assessed in the catalytic reduction of Cr(VI) to Cr(III) in aqueous solution in the presence of formic acid (HCOOH) as a reducing agent. We found that Pd/GO nanocatalyst exhibits high activity (TOF=3.6 mol Cr2 O7 2− /mol Pd×min) and reusability (> 90% at 5 th reuse) in this catalytic transformation at room temperature. Abstract : Palladium nanoparticles supported on graphene oxide act as highly active and reusable nanocatalyst for the catalytic reduction of hexavalent chromium(VI) in the presence of formic acid as reducing agent at room temperature.